Prediction of intrauterine inflammation in patients with preterm premature rupture of membranes at 28 to 34 weeks of gestation - Yunxia Wang; Yanyun Xu; Shan Wang; Xiaoli Wang; Yongzhong Gu; Ye Zhang (IMR Press, 2022)
Background: To analyze the influence of white blood cells (WBC), serum C-reactive protein (CRP), procalcitonin (PCT), and other risk factors on the prognosis of patients with preterm premature rupture of membranes (PPROM) from 28 to 34 weeks of gestation. Methods: We performed a retrospective study of 425 patients with PPROM from 28 to 34 weeks of gestation who delivered infants at Shandong Provincial Hospitals between January 1, 2013 and December 31, 2019. Risk factors for puerperal infection were analyzed using a logistic regression model. A receiver operating characteristic (ROC) curve was constructed, and the area under the curve (AUC) was estimated. Results: Of the 425 patients (mean ± SD age, 34.69 ± 5.55 years), 104 (24.47%) had chorioamnionitis. The CRP level (odds ratio [OR], 1.009; 95% Confidence Interval (CI), 1.003-1.014; P = 0.002), WBC count (OR, 1.170; 95% CI, 1.092-1.254; P < 0.001) and gestational age (OR, 0.772; 95% CI, 0.648-0.921; P = 0.004) were risk factors of chorioamnionitis. Patients who did not undergo previous cesarean section had twice the risk of developing chorionic inflammation (P = 0.022). The cut-off value of CRP level for prediction of chorioamnionitis was 19.69 mg/L with a sensitivity of 65.4%, a specificity of 75.7%, a positive predictive value (PPV) of 46.58%, and a negative predictive value (NPV) of 90.24%. The cut-off value of WBC count was 12.99 × 109/L with a sensitivity of 62.4%, a specificity of 65.8%, a PPV of 36.65%, and an NPV of 84.61%. The cut-off value of PCT level was 0.054 ng/mL with a sensitivity of 81.0%, a specificity of 75.7%, a PPV of 32.08%, and an NPV of 90.67%. The AUC for CRP was 0.731. Conclusions: Study results suggested that CRP level (<19.69 mg/L), WBC count (<12.99 × 109/L) and PCT level (<0.054 ng/mL) had good NPVs for chorioamnionitis, whereas their PPVs were low. The CRP level was found to have the most accurate prediction of chorioamnionitis among patients with PPROM from 28 to 34 weeks of gestation.